The impact of international trade factors on wage differential in Asia countries: new panel data evidence - Ng, Ching Teng (2024)
International trade is vital to the global economy, contributing to global prosperity and job growth. By driving the growth of the global economy, it provides employment opportunities for people in different industries in various countries. In this study, data from 30 Asian countries from 2015 to 2020 will be used to explore how International Trade affects Wage Differential. Therefore, in order to continue to promote wage equality, it is urgent to clarify the mechanism by which International Trade affects the Wage Differential. This study will look at Trade Openness, Population Gender Ratio (female to male), and Foreign Direct Investment (FDI) three aspects of in-depth analysis of International Trade impact on the Wage Differential of the internal mechanism. The contribution and positive and negative impacts caused by the level, thus providing support for how International Trade can better promote wage equality.